Development and Evaluation of a Recovery College Fidelity Measure. (June 2019) - Toney, Rebecca; Knight, Jane; Hamill, Kate; Taylor, Anna; Henderson, Claire; Crowther, Adam; Meddings, Sara; Barbic, Skye; Jennings, Helen; Pollock, Kristian; Bates, Peter; Repper, Julie; et al.
Objective: Recovery Colleges are widespread, with little empirical research on their key components. This study aimed to characterize key components of Recovery Colleges and to develop and evaluate a developmental checklist and a quantitative fidelity measure. Methods: Key components were identified through a systematized literature review, international expert consultation ( n = 77), and semistructured interviews with Recovery College managers across England ( n = 10). A checklist was developed and refined through semistructured interviews with Recovery College students, trainers, and managers ( n = 44) in 3 sites. A fidelity measure was adapted from the checklist and evaluated with Recovery College managers ( n = 39, 52%), clinicians providing psychoeducational courses ( n = 11), and adult education lecturers ( n = 10). Results: Twelve components were identified, comprising 7 nonmodifiable components (Valuing Equality, Learning, Tailored to the Student, Coproduction of the Recovery College, Social Connectedness, Community Focus, and Commitment to Recovery) and 5 modifiable components (Available to All, Location, Distinctiveness of Course Content, Strengths Based, and Progressive). The checklist has service user student, peer trainer, and manager versions. The fidelity measure meets scaling assumptions and demonstrates adequate internal consistency (0.72), test-retest reliability (0.60), content validity, and discriminant validity. Conclusions: Coproduction and an orientation to adult learning should be the highest priority in developing Recovery Colleges. The creation of the first theory-based empirically evaluated developmental checklist and fidelity measure (both downloadable atresearchintorecovery.com/recollect ) for Recovery Colleges will help service users understand what Recovery Colleges offer, will inform decision making by clinicians and commissioners about Recovery Colleges, and will enable formal evaluation of their impact on students.